Policies to Address the Refugee Crisis in Europe Related to Russia's Invasion of Ukraine - Bird, Nicolo (IMF Notes; IMF Notes, 2022)
Refugees from Ukraine face multiple vulnerabilities, with many requiring humanitarian assistance to meet basic needs. In response to Russia's invasion of Ukraine, host countries in Europe and beyond have adopted measures to support refugees, including residency rights, free movement across countries, access to labor markets and integration policies, health and education services, housing options, banking services, and social protection systems. Drawing on previous IMF work on the economic challenges of refugees, this note provides an overview of policy responses needed to provide effective support to refugees fleeing Ukraine.